2021
DOI: 10.1186/s13256-021-02899-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary coinfection of Mycobacterium tuberculosis and Tropheryma whipplei: a case report

Abstract: Background We diagnosed a clinical case of pulmonary infection involving Mycobacterium tuberculosis and Tropheryma whipplei in a patient with acute respiratory distress syndrome. The diagnosis was assisted by metagenomic next-generation sequencing of bronchoalveolar lavage fluid. Case presentation A 44-year-old Han Chinese inmate was transferred to the emergency department because of dry cough, chest tightness, and shortness of breath. The patient’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Moreover, we also found that immunocompromised patients were more likely to be diagnosed with pneumonia, suggesting that T. whipplei should be considered more as a pathogen when detected in BALF in immunocompromised patients with clinical symptoms. Mycobacterium tuberculosis complex and T. whipplei co-infection or detection were occasionally reported in other studies ( Lagier et al., 2016 ; Zhu et al., 2021 ). However, our study found that Mycobacterium tuberculosis complex was the most common pathogenic bacteria detected together, and a considerable number of patients (34.3%) were diagnosed as reactivation pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, we also found that immunocompromised patients were more likely to be diagnosed with pneumonia, suggesting that T. whipplei should be considered more as a pathogen when detected in BALF in immunocompromised patients with clinical symptoms. Mycobacterium tuberculosis complex and T. whipplei co-infection or detection were occasionally reported in other studies ( Lagier et al., 2016 ; Zhu et al., 2021 ). However, our study found that Mycobacterium tuberculosis complex was the most common pathogenic bacteria detected together, and a considerable number of patients (34.3%) were diagnosed as reactivation pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 61%
“…Li et al reported a case of Severe pneumonia in adults caused by T.whipplei and Candida albicans infection [40] . Yan et al found that T.whipplei hide in an AIDS Patient With Pneumocystis Pneumonia [41] .The co-infection of Mycobacterium tuberculosis complex and T.whipplei has occasionally been reported in other studies [42][43] . And our study found that Klebsiella pneumoniae, Acinetobacter baumannii and Pneumocystis yersiniae were the most common pathogenic bacteria tested together.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 2c [12] : Chest CT imaging shown diffuse miliary patchy high-density shadows in both lungs. Figure 2d [17] : Chest CT imaging shown groundglass high-density shadow in both lungs. Figure 2e [18] : Chest CT imaging shown patchy high-density shadow in the left lung and right lung lower lobe, showing bronchial shadows, and small bilateral pleural effusions.…”
Section: Declarationsmentioning
confidence: 99%
“…The age, gender, underlying diseases, clinical presentations, laboratory examinations, pulmonary imaging , treatment strategy, and outcomes of patients were retrospectively collected [12][13][14][15][16][17][18][19][20][21][22] . The relevant pictures of the article have been authorized by the original author or publisher (Supplementary material 1).…”
Section: Data Collectionmentioning
confidence: 99%